Technoeconomic assessment of hydrothermal liquefaction oil from lignin with catalytic upgrading for renewable fuel and chemical production. Issue 1 (24th July 2018) - Funkenbusch, LiLu T.; Mullins, Michael E.; Vamling, Lennart; Belkhieri, Tallal; Srettiwat, Nattapol; Winjobi, Olumide; Shonnard, David R.; Rogers, Tony N.
Abstract : Lignin is a readily available by‐product of the Kraft pulping process, and may be processed via hydrothermal liquefaction (HTL) to produce a bio‐oil suitable for cofeeding into a petroleum refinery hydrotreatment unit. HTL of lignin is performed in near‐critical water and, in addition to the bio‐oil, produces an aqueous organic and solid char phase. The aqueous organics are primarily phenolics, which may be converted into valuable coproducts via liquid–liquid extraction and hydrotreatment to benzene, toluene, ethylbenzene, and xylenes (BTEX) compounds. Three technological scenarios were developed: a current technology case, a state‐of‐the‐art research case, and an optimal case based on product targets provided by refiners. For a large Kraft pulp mill (400 metric tons/day of dry lignin), a renewable fuel production of 65–70 million L/year, with capital costs of 114–125 million and a final per liter cost of 0.41–0.44 were estimated. The BTEX coproduct yield ranged from 16.8–18.0 million L/year. An economic analysis of the process revealed that the hydrotreatment steps have the highest installed capital costs, while the liquid–liquid extraction process is the largest operating cost. Based on these results, the minimum selling price (MSP) of the biofuel is between 3.52 and 3.86/gallon, and the MSP of BTEX is between 1.65 and 2.00 per liter. With current technology, coproduction of BTEX does not offset the cost of biofuel production. Improved technology to further lower bio‐oil oxygen content and decrease both capital and operating costs are needed to make HTL‐based fuels competitive with fossil fuel‐based options. This article is categorized under: Energy Research & Innovation > Science and Materials Bioenergy > Economics and Policy Bioenergy > Systems and Infrastructure Abstract : The technoeconomic assessment of hydrothermal liquefaction of lignin from a pulp mill for diesel fuel and commodity chemical production.